First Report of Single Pelvic Fin in Hemiramphus far (Family: Hemiramphidae) from Indian Waters - Anwesha Behera; Jeevan T.M.; Subal Kumar Roul; A. Pavan kumar; A.K. Jaiswar (Journal of Indian Fisheries Association, 2020)
This is the ﬁrst report of morphological abnormalities in Hemiramphus far (Forsskal, 1775) from Tamilnadu, S-E coast of India. A young female of 236mm SL, captured in a gill-net, was found with single pelvic fin. The comparison of morphological characters of normal specimens and abnormal specimen did not reveal any diﬀerence. Thus, it is concluded that stress during ontogenic growth aﬀected the development of the second pelvic fin and this deficiency did not interfere in survival till adulthood.